2017
DOI: 10.1016/j.jsc.2016.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Computing minimal interpolation bases

Abstract: International audienceWe consider the problem of computing univariate polynomial matrices over afield that represent minimal solution bases for a general interpolationproblem, some forms of which are the vector M-Pad\'e approximation problem in[Van Barel and Bultheel, Numerical Algorithms 3, 1992] and the rationalinterpolation problem in [Beckermann and Labahn, SIAM J. Matrix Anal. Appl. 22,2000]. Particular instances of this problem include the bivariate interpolationsteps of Guruswami-Sudan hard-decision and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
82
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(82 citation statements)
references
References 41 publications
(78 reference statements)
0
82
0
Order By: Relevance
“…Although in a slightly different context, we remark that a linear algebra point for normal form computation can be found for the commutative case already in [13, Sections 6.7.1 and 6.72]. More recently, in [3] and [12,Section 7] it is shown that the shifted Popov basis of a k[x]-module given by equations exactly corresponds to some specific rows in a reduced row echelon form of the left nullspace of a constant matrix with much larger dimension than the original polynomial equations. The algorithm we present here is based on the linearization technique of Labhalla, Lombardi and Marlin [14].…”
Section: Introductionmentioning
confidence: 84%
“…Although in a slightly different context, we remark that a linear algebra point for normal form computation can be found for the commutative case already in [13, Sections 6.7.1 and 6.72]. More recently, in [3] and [12,Section 7] it is shown that the shifted Popov basis of a k[x]-module given by equations exactly corresponds to some specific rows in a reduced row echelon form of the left nullspace of a constant matrix with much larger dimension than the original polynomial equations. The algorithm we present here is based on the linearization technique of Labhalla, Lombardi and Marlin [14].…”
Section: Introductionmentioning
confidence: 84%
“…3] which returns s-Popov bases and is about twice slower than PM-Basis; making this overhead negligible for some usual cases is future work. For completeness, we handle general approximants (with one modulus per column of F) by an iterative approach from [2,47]; faster algorithms are more complex [23][24][25] and use partial linearization techniques.…”
Section: Approximant Bases and Interpolant Basesmentioning
confidence: 99%
“…. This definition is a specialization of those in [3,24], which consider n sets of points, one for each of the n columns of E 1 , . .…”
Section: Interpolant Bases For Matricesmentioning
confidence: 99%
See 1 more Smart Citation
“…5.3 and 6.14). Jeannerod et al (2017) gave an algorithm achieving a cost similar to that in the first item above, in the more general context of Eq. (2) and thus covering the case of arbitrary orders as well; the cost bound above improves upon that given in (ibid., Thm.…”
Section: Introductionmentioning
confidence: 95%